PERENCANAAN SUMBER DAYA DOSEN TETAP BUKAN PNS PADA UNIVERSITAS ISLAM NEGERI ANTASARI BANJARMASIN - Saleh, Muhammad; Irawanto, Irawanto; Priono , Singgih (PPPM STIA Amuntai, 2019)
This study presents the planning of permanent non-civil servant lecturer resources at the Antasari Banjarmasin State Islamic University in connection with the transformation of status changes from IAIN to UIN. The purpose of this study is to find out how the planning of permanent lecturer resources is not a civil servant at Antasari Banjarmasin State Islamic University, and to find out what are the obstacles faced in the planning of non-PNS permanent lecturer resources at the Antasari State Islamic University Banjarmasin. This type of research is field research with a qualitative research approach (qualitaitive research). The results showed that the planning of permanent lecturer resources not civil servants at Antasari Banjarmasin State Islamic University has been implemented well in this case there was a significant increase in permanent lecturers and carried out in accordance with statutory regulations as regulated in Minister of Religion Regulation Number 3 of 2016 and Decree Director General of Islamic Education Number 844 of 2016 concerning Guidelines for the Appointment of Non-PNS Lecturers at State Islamic Religious Colleges (PTKIN). The non-PNS lecturer resource planning activities were carried out systematically in the form of job analysis, recruitment, selection, placement and development, the constraints faced in the planning of permanent non-PNS lecturer resources. and selection of non-PNS permanent lecturers is carried out in stages by adjusting the available budget, linearity and the ratio of lecturers to students who are not in accordance with the study program and weak management of development.